Safety and feasibility of orbital atherectomy for the treatment of calcified coronary lesions. Issue 7 (5th March 2013) - Parikh, Keyur; Chandra, Praveen; Choksi, Nishit; Khanna, Puneet; Chambers, Jeffrey
<x xml:space="preserve">Abstract</x> Objective: The ORBIT I trial evaluated the safety and performance of an orbital atherectomy system (OAS) for the treatment of de novo calcified coronary lesions. Background: Severely calcified coronary arteries pose an ongoing treatment challenge. Stent placement in calcified lesions can result in stent under expansion, malapposition, and procedural complications. OAS treatment may change calcified lesion compliance to reduce procedural complications and facilitate stent placement. Methods: The ORBIT I trial, a prospective, nonrandomized study, was conducted in two centers in India. Fifty patients with de novo calcified coronary lesions were enrolled. Patients were treated with the OAS followed by stent placement. Results: The average age of the patients was 57.4 years and 90% were male. Mean lesion length was 13.4 mm. The average number of OAS devices used per patient was 1.3. Device success was 98%, and procedural success was 94%. The cumulative major adverse cardiac event rate was 4% in‐hospital (two non–Q‐wave myocardial infarctions), 6% at 30 days (one additional non–Q‐wave myocardial infarction leading to target lesion revascularization), and 8% at 6 months (one additional event of cardiac death). Angiographic complications were observed in seven patients (six dissections and one perforation). Conclusion: The ORBIT I trial suggests that the OAS may offer an effective method to change compliance of calcified coronary lesions to facilitate optimal stent placement in these difficult to treat patients. A larger trial is required to establish safety and overall effectiveness of the OAS in treating calcified coronary lesions. © 2012 Wiley Periodicals, Inc.